Controlled diet in phenylketonuria and hyperphenylalaninemia may cause serum selenium deficiency in adult patients: the Czech experience - Procházková, Dagmar; Jarkovský, Jiří; Vinohradská, Hana; Konečná, Petra; Machačová, Lucie; Doležel, Zdeněk (Biological trace element research, 2013)
Phenylketonuria is an inherited disorder of metabolism of the amino acid phenylalanine caused by a deficit of the enzyme phenylalanine hydroxylase. It is treated with a low-protein diet containing a low content of phenylalanine to prevent mental affection of the patient. Because of the restricted intake of high-biologic-value protein, patients with phenylketonuria may have lower than normal serum concentrations of pre-albumin, selenium, zinc and iron. The objective of the present study was to assess the compliance of our phenylketonuric (PKU) and hyperphenylalaninemic (HPA) patients; to determine the concentration of serum pre-albumin, selenium, zinc and iron to discover the potential correlation between the amount of proteins in food and their metabolic control. We studied 174 patients of which 113 were children (age 1-18), 60 with PKU and 53 with HPA and 61 were adults (age 18-42), 51 with PKU and 10 with HPA. We did not prove a statistically significant difference in the concentration of serum pre-albumin, zinc and iron among the respective groups. We proved statistically significant difference in serum selenium concentrations of adult PKU and HPA patients (p = 0.006; Mann-Whitney U test). These results suggest that controlled low-protein diet in phenylketonuria and hyperphenylalaninemia may cause serum selenium deficiency in adult patients.
Keywords: Male; fenylketonurie; Child, Preschool; Adolescent; Infant; Česká republika; Child; dítě; Adult; Phenylketonurias; Selenium; Prospective Studies; dospělí; mužské pohlaví; Diet, Protein-Restricted; mladiství; Czech Republic; předškolní dítě; selen; lidé; ženské pohlaví; Humans; kojenec; nízkoproteinová dieta; Female; prospektivní studie